Bringing strategy back : how strategic shock absorbers make planning relevant in a world of constant change - Sampler, Jeffrey L. (Jossey-Bass business & management series., 2015)
"Executives talk about developing innovative new strategies. They go to conferences on change and hire consultants to manage strategic reinvention. In short, they equate great strategy with great performance. Yet, all too often, strategic change occurs in reaction mode. Sales are down and market share is declining. Profitability is worsening. New types of competitors enter the fray and permanent turbulence disrupts business. Only then do we find we can rally the urgency and the focus to drive business in new and better directions. The problem with reactive planning, of course, is that it happens too late. You find yourself playing catch-up. The damage is done and someone else claims the competitive advantage. The challenge is to make strategic planning proactive and preemptive as a matter of course. That type of fast, fluid approach requires a mind shift, to be sure, but it also requires a new set of tools.This book offers both. It presents a new ethos for thinking about strategy and a practical response to chaos. Even better, it contains a rich set of new ideas that come together to form a critical model to enable strategic change. In essence, it redefines how organizations approach strategic planning. More specifically, it addresses a strategic planning process that has been made obsolete by permanent change and turbulence. It does so in three ways:1. A Current Diagnosis of the Problem: The book argues persuasively that the conventional tools of strategic planning have been made irrelevant by four overlapping challenges: opportunities are getting smaller, growth across markets is uneven, competition is difficult to identify, and the window of opportunity is closing faster. It goes on to evaluate the traditional strategy planning process and explain how companies can manage change efficiently in this rapidly shifting, turbulent environment. 2. A Prescriptive Solution: The book presents a novel, research-based model for strategic change, made-up of four general components: Accuracy, Agility, Absorbing Impact, and Anticipate the Future. These components come together to form a framework that is robust yet accessible, enabling organizations to be proactive and dynamic, not reactive. 3. New Examples that Illustrate the Entire Model: The cases in this book demonstrate all of the ideas in the framework, as opposed to proving one piece at a time. This suggests two key insights. First, the findings in this book are robust and shared across a variety of industries, companies of different sizes, and countries. Second, the ideas in this book are part of an integrated system-if just one or two ideas are implemented the results will not be the same"--